2006
DOI: 10.1103/physreve.74.051907
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence versus extinction in the stochastic cyclic Lotka-Volterra model

Abstract: Cyclic dominance of species has been identified as a potential mechanism to maintain biodiversity, see, e.g., B. Kerr, M. A. Riley, M. W. Feldman and B. J. M. Bohannan ͓Nature 418, 171 ͑2002͔͒ and B. Kirkup and M. A. Riley ͓Nature 428, 412 ͑2004͔͒. Through analytical methods supported by numerical simulations, we address this issue by studying the properties of a paradigmatic non-spatial three-species stochastic system, namely, the "rock-paper-scissors" or cyclic Lotka-Volterra model. While the deterministic a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
330
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 242 publications
(354 citation statements)
references
References 40 publications
20
330
1
3
Order By: Relevance
“…Differences in birth and death rates Eqs. (13) and (26) are negligible for small population size. The arrest of the dynamics only becomes effective at later times where an increase in population size implies a significantly declining birth rate.…”
Section: E the Dormancy Scenariomentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in birth and death rates Eqs. (13) and (26) are negligible for small population size. The arrest of the dynamics only becomes effective at later times where an increase in population size implies a significantly declining birth rate.…”
Section: E the Dormancy Scenariomentioning
confidence: 99%
“…This comprises, for example, the prisoner's dilemma, the snowdrift game and other games in well-mixed populations [11][12][13]15]. It further ranges from the role of spatial arrangements and network interactions [16][17][18][19][20][21][22][23][24][25] via cyclic dominance [7,[26][27][28][29][30][31][32][33], structured populations [34,35], modified update rules [36,37], multiplayer games [38], and evolutionary algorithms [39] to the influence of internal and external fluctuations [40][41][42][43][44][45]. While these models consider a wide range of evolutionary aspects, they mostly rely on one key assumption, a decoupled, constant population size.…”
Section: Introductionmentioning
confidence: 99%
“…In experiments with Escherichia coli, for example, it has been shown that arranging the bacteria on a Petri dish is crucial for keeping all three competing strains alive [8,36]. Accordingly, simulations of spatial rock-paper-scissors and related games of cyclic dominance have a long and fruitful history [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56], which is firmly rooted in methods of statistical physics. In general, if the mobility in the population is sufficiently small [7], the spatial rock-paper-scissors game leads to the stable coexistence of all three competing strategies, whereby the coexistence is maintained by the spontaneous formation of complex spatial patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps suprisingly this includes even long-range processes [16,17], generalizations to 'smart' predators and prey who respectively follow / evade the other species [11,14], and a variation where the predation reaction is split up into two separate and independent processes [23]. Indeed, already a zero-dimensional stochastic predator-prey model exhibits prominent population oscillations driven by the inevitable internal reaction noise [22]; such finitesize fluctuations also drastically affect the properties of, e.g., the three-species cyclic Lotka-Volterra model [25].…”
Section: Introductionmentioning
confidence: 99%